Revision of the Australian bee subgenus Leioproctus (Euryglossidia) Cockerell, 1910 (Hymenoptera: Colletidae: Neopasiphaeinae) - Michael Batley (Records of the Australian Museum)
The subgenus Leioproctus (Euryglossidia) is a large group of Australian Neopasiphaeine bees in need of revision. Forty-five new species are described, bringing the number of recognised names to 60. Four new synonymies are proposed, one species is transferred to Leioproctus (Colletellus) and one remains species inquirenda. No change is required in the diagnostic characters of the group, which is recognised by the presence of two submarginal cells in the forewing and a short jugal lobe on the hind wing. The new species demonstrate continuous character variation from rough to polished integument, iridescent to non-iridescent colour, sparse to close scopal hair of females without distinct breaks between subgroups. Detailed molecular investigation will be required before further subdivision is contemplated. Illustrations of diagnostic characters and identification keys are included.